Adrenal crisis and mortality rate in adrenal insufficiency and congenital adrenal hyperplasia - Lia Mesquita Lousada; Berenice B. Mendonca; Tania A. S. S. Bachega (Archives of Endocrinology and Metabolism, 2021)
ABSTRACT Primary adrenal insufficiency (PAI) is characterized by the inability of the adrenal cortex to produce sufficient amounts of glucocorticoids and/or mineralocorticoids. Addison's disease (AD) and congenital adrenal hyperplasia (CAH) are the most frequent disorders in adults and children, respectively. Despite the diagnostic advances and the availability of glucocorticoid and mineralocorticoid replacements, adrenal crisis (AC) is still a potentially lethal condition contributing to the increased mortality, not only during the first year of life, but also throughout life. Failure in increasing glucocorticoid doses during acute stress, when greater amounts of glucocorticoids are required, can lead to AC and an increase morbimortality rate of PAI. Considering a mortality rate of 0.5 per 100 patient years, up to 1,500 deaths from AC are expected in Brazil in the coming decade, which represents an alarming situation. The major clinical features are hypotension and volume depletion. Nonspecific symptoms such as fatigue, lack of energy, anorexia, nausea, vomiting, and abdominal pain are common. The main precipitating factors are gastrointestinal diseases, other infectious disease, stressful events (e.g., major pain, surgery, strenuous physical activity, heat, and pregnancy), and withdrawal of glucocorticoid therapy. Suspected AC requires immediate therapeutic action with intravenous (iv) hydrocortisone, fluid infusion, monitoring support, and antibiotics if necessary. AC is best prevented through patient education, precocious identification and by adjusting the glucocorticoid dosage in stressor situations. The emergency card, warning about acute glucocorticoid replacement, has high value in reducing the morbidity and mortality of AC.